2022
DOI: 10.3389/fcell.2022.832314
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase 3 Deficiency Protects From Noise-Induced Sensorineural Hearing Loss

Abstract: The reactive oxygen species (ROS)-generating NADPH oxidase NOX3 isoform is highly and specifically expressed in the inner ear. NOX3 is needed for normal vestibular development but NOX-derived ROS have also been implicated in the pathophysiology of sensorineural hearing loss. The role of NOX-derived ROS in noise-induced hearing loss, however, remains unclear and was addressed with the present study. Two different mouse strains, deficient in NOX3 or its critical subunit p22phox, were subjected to a single noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…However, middle ear delivery failed to reach its target and led to adverse effects on animal hearing. Based on the results previously obtained from NOX3 knockout mice (12,14,15), we hypothesize that mice receiving NOX3 siRNA will be at least partially protected from noise-induced hearing loss. However, translation of such a concept toward clinical application in humans will request important efforts to achieve efficient intracochlear siRNA delivery without inducing hearing loss (19-21).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, middle ear delivery failed to reach its target and led to adverse effects on animal hearing. Based on the results previously obtained from NOX3 knockout mice (12,14,15), we hypothesize that mice receiving NOX3 siRNA will be at least partially protected from noise-induced hearing loss. However, translation of such a concept toward clinical application in humans will request important efforts to achieve efficient intracochlear siRNA delivery without inducing hearing loss (19-21).…”
Section: Introductionmentioning
confidence: 85%
“…We have also demonstrated that in an aging mouse model, NOX3 deficiency prevents from excitotoxic cochlear damage associated to cochlear aging, showing significant protection of hearing and cochlear morphology (14). Furthermore, NOX3-deficient mice exhibit significantly better hearing recovery following noise trauma compared to their wild-type (WT) littermates (15). Interestingly, contrasting with the initial hypothesis of a direct oxidative stress mediated damage, the consequences of NOX3 activity are more complex, involving specific redox signaling pathways.…”
Section: Introductionmentioning
confidence: 92%
“…PMCA2w/a missense mutation causes deafness and balance disorders in humans (Bortolozzi and Mammano, 2018) Nox (NADPH oxidases) Expression in the cochlea and vestibule (Kiss et al, 2006;Xu et al, 2021) The main otolith components and factors necessary for calcium carbonate crystallization (Xu et al, 2021) The absence of NOX3 enhances hearing recovery after noise trauma (Rousset et al, 2022) CA (carbonic anhydrase) Expression in the cochlea and vestibule (Tohse and Mugiya, 2001;Matsumoto et al, 2017;Liu et al, 2022) Maintaining the right pH to promote otolith development and regulate otolith growth (Tohse et al, 2006;Matsumoto et al, 2017) CA inhibitors can cause hearing loss, and inhibit calcification of otoliths (Tohse and Mugiya, 2001;Liu et al, 2022) human hearing and vestibular disorders, and DFNA9, is secreted by small specialized areas of vestibular system epithelia whereby cells secrete Cochlin to the ear lumen and base of the basal lamina. Cochlin secreted from the base diffuses along the basal surface of vestibular epithelium, and is apically secreted and integrated into otolith.…”
Section: Pmca2mentioning
confidence: 99%
“…The absence of functional NOX3 enhances the recovery phase of hearing after noise trauma. This opens an interesting clinical window for pharmacological or molecular interventions aimed at preventing noise-induced hearing loss ( Rousset et al, 2022 ).…”
Section: Important Factors Affecting the Formation And Maintenance Of...mentioning
confidence: 99%
“…leading to hearing loss(Rousset et al 2022). TGF-β gene has three isoforms, I, II, and III, expressed in the cochlea(Kim et al 2006): TGF-β2 gene is expressed in the cochlear epithelium, and TGF-β1 and TGF-3 genes are expressed in both epithelial and mesenchymal tissues(Kim et al 2006).…”
mentioning
confidence: 99%